2014
DOI: 10.1111/jvec.12116
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Florida Aedes aegypti and Aedes albopictus to dengue viruses from Puerto Rico

Abstract: Locally acquired dengue cases in the continental U.S. are rare. However, outbreaks of dengue-1 during 2009, 2010, and 2013 in Florida and dengue-1 and -2 in Texas suggest vulnerability to transmission. Travel and commerce between Puerto Rico and the U.S. mainland is common, which may pose a risk for traveler-imported dengue cases. Mosquitoes were collected in Florida and used to evaluate their susceptibility to dengue viruses (DENV) from Puerto Rico. Aedes aegypti and Ae. albopictus were susceptible to virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…aegypti, but less susceptible to dissemination and transmission of the virus. [26][27][28][29] One study, which exposed mosquitoes by direct blood feeding on viremic patients, demonstrated a similar minimum 50% infectious dose (MID 50 ) required to infect both Ae. species, but Ae.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti, but less susceptible to dissemination and transmission of the virus. [26][27][28][29] One study, which exposed mosquitoes by direct blood feeding on viremic patients, demonstrated a similar minimum 50% infectious dose (MID 50 ) required to infect both Ae. species, but Ae.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus [149152], Ae. aegypti [149,150,152160] and Cx. quinquefasciatus [154], although the latter was not identified as a competent vector species experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…albopictus were collected from water-filled containers in Key West (Old Town historic district) and Vero Beach, FL, respectively. Mosquitoes were reared using methods described by Alto et al (2014) . Briefly, mosquitoes were kept at 26-28°C and 60-80% relative humidity in a climate controlled room and a light:dark cycle of 14:10 hours.…”
Section: Methodsmentioning
confidence: 99%
“…aegypti and Ae. albopictus ( Alto et al 2014 ). The results showed no significant differences in infection or dissemination rates between Ae.…”
mentioning
confidence: 99%
See 1 more Smart Citation